Inflammatory status and severity of disease in dengue patients are associated with lipoprotein alterations. (2023)
The triggering of severe dengue has been associated with an exacerbated inflammatory process characterized by the production of pro-inflammatory cytokines such as IL-1/IL-18, which are the product of inflammasome activation. Furthermore, alteration in the levels of high-density (HDL) and low-density lipoproteins (LDL) has been observed; and HDL are known to have immunomodulatory properties, including the regulation of inflammasomes. While HDL would be expected to counteract hyperactivation of the inflammasome, the relationship between HDL and dengue severity, has not previously been explored.